The Colosseum - Noll, Elizabeth (Seven wonders of the modern world (Bellwether Media), 2021)
Initiates a tour of the Roman Colosseum, showcasing photographs and a map and describing its history, uses, and renovation as a tourist attraction. Includes fact boxes, a timeline, statistical chart, a glossary, and resources for further information.